Rock Salt Properties for Gas Storage in Mined Caverns: Part I–Short-Term Deformation and Yield, Long-Term Creep, and Gas Sealing Capacity - J. Sarout; M. Sari; L. Esteban; P. P. Mandal; J. Bourdet; D. Nguyen; J. Strand; E. Frery; L. Imbert; A. Francois; L. Langhi; D. Mallants (Rock Mechanics and Rock Engineering, 2026)
Deep rock salt formations can be drilled and solution-mined into caverns for permanent waste disposal, or temporary energy storage (natural gas/compressed air/hydrogen) to alleviate the intermittency of wind/solar energy. We report here the results of the laboratory appraisal of the key properties of a thick Devonian rock salt formation in the Canning Basin (Western Australia). Two representative but contrasting lithofacies were identified: a clean lithofacies made of nearly pure halite, and a dirty lithofacies comprising anhydrite, and dolomite/quartz inclusions. On each lithofacies, we conducted a mineralogical, microstructural and petrophysical characterisation, and a long-term four-stage triaxial test to simulate the impact of depth and anthropogenic stress perturbations. Strains and ultrasonic P-/S-wave velocities were monitored, and at specific stages of the triaxial test, long-term gas transmissivity and creep tests were conducted for up to 16 and 42 days, respectively. At all the triaxial stresses explored, including the in-situ conditions, the oven-dry clean salt facies exhibits a typical gas permeability of 5.10 –5 mD = 5.10 –20 m 2 , whereas the dirty salt is 100 to 1000 times more permeable to gas. The estimated steady-state creep rates are consistent with the extensive collection of literature data also reported here. The dominant creep mechanism is likely dislocation glide, complemented by frictional sliding where damage might exist. Pressure-solution creep is probably not dominant here, especially within the testing time scale. However, water is likely present in deep salt bodies and around man-made salt caverns, promoting overall creep through pressure-solution, and damage healing, hence reducing gas permeability even further.

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Comparative Description and Analysis of Oyster Aquaculture in Selected Atlantic Regions: Production, Market Dynamics, and Consumption Patterns - Johannes A. Iitembu; Daniel Fitzgerald; Themistoklis Altintzoglou; Pierre Boudry; Peter Britz; Carrie J. Byron; Daniel Delago; Sophie Girard; Colin Hannon; Marcia Kafensztok; Francisco Lagreze; Jefferson Francisco Alves Legat; et al. (Fishes, 2023)
In the face of an increasing world population and a subsequent need for an increase in sustainable and healthy food production, low trophic species, such as oysters, emerge as a promising alternative. However, regional variations in oyster production techniques, market dynamics, and consumption patterns create challenges for both the global and local industry’s growth. In this study, a descriptive qualitative analysis of oyster markets across seven Atlantic regions was carried out. The Pacific oyster (Crassostrea gigas) was found to be farmed in most Atlantic regions except the US but is classified as invasive in Sweden and potentially invasive in South Africa. Other farmed and/or harvested species include native species (C. gasar and C. rhizophorae) in Brazil, the American cupped oyster (C. virginica) in the US, and the European flat oyster (Ostrea edulis) in France, Sweden, and the US. In Irish farms, Pacific oysters are primarily for export to European markets. The marine aquaculture sectors of Sweden, South Africa, and Namibia, as well as Brazil’s farming for C. gasar, were found to be underdeveloped. This study also observed a variation in licensing, property rights, and regulatory frameworks. Financial challenges for small businesses, ecological implications of seed production techniques, biosecurity risks, and public health considerations are emphasized as critical areas for attention. This study offers valuable insights into the selected markets and can serve as a useful resource for policymakers, aquaculture practitioners, and stakeholders in optimizing global shellfish industry strategies.

Tradeoffs and synergies in wetland multifunctionality: A scaling issue - P.A. Hambäck; L. Dawson; P. Geranmayeh; J. Jarsjö; I. Kačergytė; M. Peacock; D. Collentine; G. Destouni; M. Futter; G. Hugelius; S. Hedman; S. Jonsson; et al. (Science of The Total Environment, 2023)

Cardiomyocyte-specific overexpression of syndecan-4 in mice results in activation of calcineurin-NFAT signalling and exacerbated cardiac hypertrophy - Ida G. Lunde; J. Magnus Aronsen; A. Olav Melleby; Mari E. Strand; Jonas Skogestad; Bård A. Bendiksen; M. Shakil Ahmed; Ivar Sjaastad; Håvard Attramadal; Cathrine R. Carlson; Geir Christensen (Molecular Biology Reports, 2022)
Background Cardiomyocyte hypertrophy is a hallmark of cardiac dysfunction in patients with aortic stenosis (AS), and can be triggered by left ventricular (LV) pressure overload in mice by aortic banding (AB). Syndecan-4 is a transmembrane heparan sulphate proteoglycan which is found increased in the myocardium of AS patients and AB mice. The role of syndecan-4 in cardiomyocyte hypertrophy is not well understood. Purpose of the study We developed mice with cardiomyocyte-specific overexpression of syndecan-4 ( Sdc4-Tg ) and subjected these to AB to examine the role of syndecan-4 in hypertrophy and activation of the pro-hypertrophic calcineurin-NFAT signalling pathway. Methods and results Sdc4-Tg mice showed exacerbated cardiac remodelling upon AB compared to wild type (WT). At 2–6 weeks post-AB, Sdc4-Tg and WT mice showed similar hypertrophic growth, while at 20 weeks post-AB, exacerbated hypertrophy and dysfunction were evident in Sdc4-Tg mice. After cross-breeding of Sdc4-Tg mice with NFAT-luciferase reporter mice, we found increased NFAT activation in Sdc4-Tg hearts after AB. Immunoprecipitation showed that calcineurin bound to syndecan-4 in Sdc4-Tg hearts. Isolated cardiomyocytes from Sdc4-Tg mice showed alterations in Ca 2+ fluxes, suggesting that syndecan-4 regulated Ca 2+ levels, and thereby, activating the syndecan-4-calcineurin complex resulting in NFAT activation and hypertrophic growth. Similarly, primary cardiomyocyte cultures from neonatal rats showed increased calcineurin-NFAT-dependent hypertrophic growth upon viral Sdc4 overexpression. Conclusion Our study of mice with cardiomyocyte-specific overexpression of Sdc4 have revealed that syndecan-4 is important for activation of the Ca 2+ -dependent calcineurin-NFAT signalling pathway, hypertrophic remodelling and dysfunction in cardiomyocytes in response to pressure overload.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Founder effects shape linkage disequilibrium and genomic diversity of a partially clonal invader - Ben A. Flanagan; Stacy A. Krueger‐Hadfield; Courtney J. Murren; Chris C. Nice; Allan E. Strand; Erik E. Sotka (Molecular Ecology, 2021)
The genomic variation of an invasive species may be affected by complex demographic histories and evolutionary changes during the invasion. Here, we describe the relative influence of bottlenecks, clonality, and population expansion in determining genomic variability of the widespread red macroalga Agarophyton vermiculophyllum . Its introduction from mainland Japan to the estuaries of North America and Europe coincided with shifts from predominantly sexual to partially clonal reproduction and rapid adaptive evolution. A survey of 62,285 SNPs for 351 individuals from 35 populations, aligned to 24 chromosome‐length scaffolds indicate that linkage disequilibrium (LD), observed heterozygosity ( H o ), Tajima's D, and nucleotide diversity (Pi) were greater among non‐native than native populations. Evolutionary simulations indicate LD and Tajima's D were consistent with a severe population bottleneck. Also, the increased rate of clonal reproduction in the non‐native range could not have produced the observed patterns by itself but may have magnified the bottleneck effect on LD. Elevated marker diversity in the genetic source populations could have contributed to the increased H o and Pi observed in the non‐native range. We refined the previous invasion source region to a ~50 km section of northeastern Honshu Island. Outlier detection methods failed to reveal any consistently differentiated loci shared among invaded regions, probably because of the complex A. vermiculophyllum demographic history. Our results reinforce the importance of demographic history, specifically founder effects, in driving genomic variation of invasive populations, even when localized adaptive evolution and reproductive system shifts are observed.

Explaining the worldwide distributions of two highly mobile species: Cakile edentula and Cakile maritima - Elliot C. Shaw; Rachael Fowler; Sara Ohadi; Michael J. Bayly; Rosemary A. Barrett; Josquin Tibbits; Allan Strand; Charles G. Willis; Kathleen Donohue; Philipp Robeck; Roger D. Cousens (Journal of Biogeography, 2021)
Aim If we are able to determine the geographic origin of an invasion, as well as its known area of introduction, we can better appreciate the innate environmental tolerance of a species and the strength of selection for adaptation that colonizing populations have undergone. It also enables us to maximize the success of searches for effective biological control agents. We determined the number of successful colonization events that have occurred throughout the world for two Cakile species and compared the climates from which they originated, in which they established and then spread. Location Worldwide. Taxon Sea‐Rockets ( Cakile spp.), Brassicaceae. Methods We used a high‐throughput sequencing and a genome skimming approach combined with Bayesian Inference phylogenetics to examine variation in entire chloroplast genomes and regions of nuclear ribosomal DNA within native and introduced areas. Databases were used to compare climates between native ranges and introduced regions for multiple clades within each species. Results At least seven clades have invaded different regions of the world. In most cases we were able to identify their source regions and climates. The environmental bottlenecks differed in intensity: while some clades colonized into climates that were similar to climates in their native range, other clades had a very broad innate environmental tolerance such that new invasions succeeded beyond the climate range of native populations. We found clear evidence of hybridization—specifically, chloroplast capture—between two species in Australia. Conclusions Results here show that these species are sometimes capable of colonizing in climates that are beyond the climate range of native populations. Whether successful colonization beyond native climate niches requires de novo adaptation, or whether it represents an innate broad fundamental niche requires further investigation. Cakile species provide an excellent opportunity to study replicated climate adaptation trajectories.

When and where plant‐soil feedback may promote plant coexistence: a meta‐analysis - Kerri M. Crawford; Jonathan T. Bauer; Liza S. Comita; Maarten B. Eppinga; Daniel J. Johnson; Scott A. Mangan; Simon A. Queenborough; Allan E. Strand; Katharine N. Suding; James Umbanhowar; James D. Bever (Ecology Letters, 2019)
Plant‐soil feedback (PSF) theory provides a powerful framework for understanding plant dynamics by integrating growth assays into predictions of whether soil communities stabilise plant–plant interactions. However, we lack a comprehensive view of the likelihood of feedback‐driven coexistence, partly because of a failure to analyse pairwise PSF, the metric directly linked to plant species coexistence. Here, we determine the relative importance of plant evolutionary history, traits, and environmental factors for coexistence through PSF using a meta‐analysis of 1038 pairwise PSF measures. Consistent with eco‐evolutionary predictions, feedback is more likely to mediate coexistence for pairs of plant species (1) associating with similar guilds of mycorrhizal fungi, (2) of increasing phylogenetic distance, and (3) interacting with native microbes. We also found evidence for a primary role of pathogens in feedback‐mediated coexistence. By combining results over several independent studies, our results confirm that PSF may play a key role in plant species coexistence, species invasion, and the phylogenetic diversification of plant communities.

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Invasion of novel habitats uncouples haplo‐diplontic life cycles - Stacy A. Krueger‐Hadfield; Nicole M. Kollars; James E. Byers; Thomas W. Greig; Mareike Hammann; David C. Murray; Courtney J. Murren; Allan E. Strand; Ryuta Terada; Florian Weinberger; Erik E. Sotka (Molecular Ecology, 2016)
Baker's Law predicts uniparental reproduction will facilitate colonization success in novel habitats. While evidence supports this prediction among colonizing plants and animals, few studies have investigated shifts in reproductive mode in haplo‐diplontic species in which both prolonged haploid and diploid stages separate meiosis and fertilization in time and space. Due to this separation, asexual reproduction can yield the dominance of one of the ploidy stages in colonizing populations. We tested for shifts in ploidy and reproductive mode across native and introduced populations of the red seaweed Gracilaria vermiculophylla . Native populations in the northwest Pacific Ocean were nearly always attached by holdfasts to hard substrata and, as is characteristic of the genus, haploid–diploid ratios were slightly diploid‐biased. In contrast, along North American and European coastlines, introduced populations nearly always floated atop soft‐sediment mudflats and were overwhelmingly dominated by diploid thalli without holdfasts. Introduced populations exhibited population genetic signals consistent with extensive vegetative fragmentation, while native populations did not. Thus, the ecological shift from attached to unattached thalli, ostensibly necessitated by the invasion of soft‐sediment habitats, correlated with shifts from sexual to asexual reproduction and slight to strong diploid bias. We extend Baker's Law by predicting other colonizing haplo‐diplontic species will show similar increases in asexuality that correlate with the dominance of one ploidy stage. Labile mating systems likely facilitate colonization success and subsequent range expansion, but for haplo‐diplontic species, the long‐term eco‐evolutionary impacts will depend on which ploidy stage is lost and the degree to which asexual reproduction is canalized.

Irisin and FNDC5: effects of 12-week strength training, and relations to muscle phenotype and body mass composition in untrained women - S. Ellefsen; O. Vikmoen; G. Slettaløkken; J. E. Whist; H. Nygaard; I. Hollan; I. Rauk; G. Vegge; T. A. Strand; T. Raastad; B. R. Rønnestad (European Journal of Applied Physiology, 2014)

Seasonal variation in mineralization rates (C-N-P-Si) of mussel Mytilus edulis biodeposits - H. M. Jansen; M. C. J. Verdegem; Ø. Strand; A. C. Smaal (Marine Biology, 2012)

Does increased abundance of sea lice influence survival of wild Atlantic salmon post‐smolt? - N. A. Hvidsten; B. Finstad; F. Kroglund; B. O. Johnsen; R. Strand; J. V. Arnekleiv; P. A. Bjørn (Journal of Fish Biology, 2007)
A synthesis of results from two projects was assessed to analyse possible influence of sea lice Lepeophtheirus salmonis on marine Atlantic salmon Salmo salar survival. During the years 1992–2004, trawling for wild migrating post‐smolts was performed in Trondheimsfjord, a fjord in which no Atlantic salmon aquaculture activity is permitted. Prevalence and intensity of sea lice infections on migrating wild post‐smolts differed between years. A correlation analysis between 1 sea‐winter (SW) Atlantic salmon catch statistics from the River Orkla (a Trondheimsfjord river) and sea lice infections on the migrating smolts in the Trondheimsfjord was not significant. Up to 2% reduction in adult returns due to sea‐lice infection was expected. In addition, experimental releases from 1996 to 1998 with individually tagged groups of hatchery‐reared Atlantic salmon smolts given protection against sea‐lice infection was performed. Higher recaptures of adult Atlantic salmon from 1998 treated smolts compared to the control group may correspond to high abundance of sea lice found on the wild smolt, and may indicate influence on post‐smolt mortality. These studies indicate that post‐smolt mortality in Trondheimsfjord is marginally influenced by sea lice infection; however, the methods for assessing wild smolt mortality might be insufficient. Higher infections of sea lice farther out in the fjord may indicate more loss in Atlantic salmon returns in some years.

Population structure in a critically endangered arctic fox population: does genetics matter? - L. DALÉN; K. KVALØY; J. D. C. LINNELL; B. ELMHAGEN; O. STRAND; M. TANNERFELDT; H. HENTTONEN; E. FUGLEI; A. LANDA; A. ANGERBJÖRN (Molecular Ecology, 2006)
The arctic fox ( Alopex lagopus ) in Scandinavia is classified as critically endangered after having gone through a severe decline in population size in the beginning of the 20th century, from which it has failed to recover despite more than 65 years of protection. Arctic foxes have a high dispersal rate and often disperse over long distances, suggesting that there was probably little population differentiation within Scandinavia prior to the bottleneck. It is, however, possible that the recent decline in population size has led to a decrease in dispersal and an increase in population fragmentation. To examine this, we used 10 microsatellite loci to analyse genetic variation in 150 arctic foxes from Scandinavia and Russia. The results showed that the arctic fox in Scandinavia presently is subdivided into four populations, and that the Kola Peninsula and northwest Russia together form a large fifth population. Current dispersal between the populations seemed to be very low, but genetic variation within them was relatively high. This and the relative F ST values among the populations are consistent with a model of recent fragmentation within Scandinavia. Since the amount of genetic variation is high within the populations, but the populations are small and isolated, demographic stochasticity seems to pose a higher threat to the populations’ persistence than inbreeding depression and low genetic variation.

Integrating biodiversity priorities with conflicting socio-economic values in the Guinean–Congolian forest region - P.H. Williams; J.L. Moore; A. Kamden Toham; T.M. Brooks; H. Strand; J. D'Amico; M. Wisz; N.D. Burgess; A. Balmford; C. Rahbek (Biodiversity and Conservation, 2003)

Parallel climate model (PCM) control and transient simulations - W. M. Washington; J. W. Weatherly; G. A. Meehl; A. J. Semtner Jr.; T. W. Bettge; A. P. Craig; W. G. Strand Jr.; J. Arblaster; V. B. Wayland; R. James; Y. Zhang (Climate Dynamics, 2000)

Sea-ice effects on climate model sensitivity and low frequency variability - G. A. Meehl; J. M. Arblaster; W. G. Strand Jr (Climate Dynamics, 2000)

Synthesis of theoretical and empirical experiences from nutrient and cyprinid reductions in Lake Ringsjön - E. Bergman; L.-A. Hansson; A. Persson; J. Strand; P. Romare; M. Enell; W. Granéli; J. M. Svensson; S. F. Hamrin; G. Cronberg; G. Andersson; E. Bergstrand (Hydrobiologia, 1999)

Nuclear DNA‐based markers for plant evolutionary biology - A. E. Strand; J Leebens‐Mack; B. G. Milligan (Molecular Ecology, 1997)
While DNA‐based markers can provide a wealth of information for the study of plant evolutionary biology, progress is limited by the lack of primers available for PCR. To overcome this limitation, we outline a protocol for developing oligonucleotide primers targeting regions of low copy‐number nuclear genes. This protocol is intended to lead to universally useful primer sets. To test our approach, we designed eight primer sets and tested their abilities to amplify targets from representatives of each dicot and one monocot subclass. Five of the eight primer sets amplified targets from at least five of the seven taxa and thus exhibited broad taxonomic usefulness; the remaining primers were rather specific, however, and amplified targets from at most three taxa. In only one primer‐taxon combination was a complex multiple‐banded amplification produced. Overall, the protocol outlined proved quite useful at identifying broadly applicable primers targeted to low copy‐number nuclear genes. Wider application of this approach should be effective at greatly increasing the amount of genetic information available for a diversity of plant nuclear genomes.

Oxygen and nitrate reduction kinetics of a nonflocculating strain of Zoogloea ramigera - S. E. Strand; A. J. McDonnell; R. F. Unz (Antonie van Leeuwenhoek, 1988)

Sectional notes - Carl H. Metzger; W. B. Ward; H. L. Cochran; J. B. R. Dickey; A. B. Strand; W. H. Friend; H. H. Zimmerley; G. S. Ralston (American Journal of Potato Research, 1939)